Pengaruh Baby Massage terhadap Kenaikan Berat Badan pada Bayi di RS Bhayangkara Banjarmasin Kalimantan Selatan - Septa Ariani; Anik Purwati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Baby massage is very useful in optimizing the growth and development of babies/children, including increasing food absorption so that babies get hungry faster and babies will breastfeed more often from their mothers, thereby increasing the baby's weight. The aim of the research was to analyze the effect of baby massage on weight gain in babies. The method used is Pre Experiment with pretest and posttest control group design. The sample in this study were 30 newborn babies at Bhayangkara Hospital, Banjarmasin. The sampling technique in this research is non-probability sampling, namely purposeve sampling. Baby massage was given for 7 days to increase the baby's weight before and after treatment analyzed using the Wilcoxαon Test. The research location was carried out at Bhayangkara Hospital. The research time was 3 months in July – September 2024. The results obtained were P value = 0.000 (α < 0.05 ) which means there is a difference in body weight before and after the massage intervention. The conclusion is that there is an effect of baby massage on weight gain in babies.